The Concept of Conflict of Interest in Lithuanian and EU Public Procurement Law and the Case-Law - Soloveičik, Deividas; Šimanskis, Karolis (Teisė, 2019)
[full article and abstract in Lithuanian; abstract in English] Until the implementation of the public procurement law reform of 2014 at the EU level and respectivlely 2017 in the Lithuanian legal environment, the legal analysis of the concept of conflicts of interest in public procurement law was scarce. Neither did the features of this phenomenon or its’ legal evaluation was the subject of any solid scholar research. However, the demand for such academic insights has recently become very bright because the courts on numerous occasions started to face the disputes with the subject conflicts of interest being at the heart of the disagreements between the litigating parties. The courts, at least in Lithuania, have even started to search the relevant answers elsewhere, including making the references to the EU judiciary for the preliminary rulings regarding this matter. Therefore, this publication is a contribution to the minimization of this “scholar thirst” in the mentioned field or at least our sincere attempt to do that.